Reconstructing Character Education for Generation Z: An Analytical Study Based on Al-Ghazali’s Ethical Framework - Abu Darda; Dinni Mawaddah; Muhammad Thoriqul Islam; Syaiful Alim; Ahmad Marzuqi; Zainur Rofik (ITScience (Information Technology and Science), 2026)
The growing urgency of character education in the digital age is closely tied to the challenges faced by Generation Z, who are shaped by rapid technological and social change that contributes to identity instability, cyberbullying, and mental health pressures. Addressing these issues requires a framework that integrates spirituality, ethical awareness, and digital literacy to cultivate integrity, responsibility, and psychological balance. This study examines Jean Twenge's technological–psychological perspective alongside Al-Ghazali's spirituality-based character framework to design a curriculum relevant to the Indonesian context. Using a systematic literature review, the research synthesizes primary works by Al-Ghazali, including Tahafut al-Falasifah, Al-Maq?ad al-Asn? f? Shar? Ma??n? Asm?? All?h al-?usn?, and I?y?’ Ul?m al-D?n with contemporary scholarship on mental health and digital ethics. Data were analyzed through thematic coding centered on five domains: character education, mental well-being, digital ethics, curriculum design, and spiritual morality, using stages of comparison, contrast, and critique. The findings propose an integrative curriculum model combining digital literacy and emotional resilience with moral purification and spiritual grounding, structured around three pillars: character formation, responsible technology engagement, and spiritual development. Although implementation presents challenges related to multicultural adaptation, teacher preparedness, and assessment of character outcomes, the model offers a holistic pathway for nurturing balanced learners. The study recommends pilot implementation in schools and Pesantren, the development of assessment tools for mental and moral growth, and longitudinal research to evaluate the long-term impact across diverse educational settings.